A low time- consuming smart FEC rate allocation scheme for robust wireless JPEG 2000 images and video - AGUEH, VICTOIRE DAMIENNE AGOSSI; atman, stefan; soude, henoc (My University, 2009)
Traditional Forward Error Correction (FEC) rate allocation schemes, used to enhance the robustness of JPEG 2000 images and video against transmission errors, are based either on Packet oriented Unequal Error Protection or on Layer oriented Unequal Error Protection. As both approaches hold their advantages, unifying them under a new framework becomes a crucial issue. In this paper, we address this issue by proposing a low time-consuming smart FEC rate allocation scheme which is based on a new paradigm of combined Packet oriented and Layer oriented FEC rate allocation scheme for efficient JPEG 2000 images and video transmission over wireless channels.
Keywords: Robustness; Forward error correction; Protection; Error correction; Error correction codes; Streaming media; Decoding; Switches; Automatic repeat request; Resilience